HUBUNGAN POLA MENSTRUASI DENGAN KEJADIAN ANEMIA PADA SISWI MA PERGURUAN ISLAM NURUL KASYSYAF (PINK) - Sunirah Sunirah; M Farhan; Ashar Prima; Amzal Mortin Andas; Indah Puspitasari; Mara Imbang Satriawan Hasiolan; Fauziah H Wada (Jurnal Ilmiah Kebidanan Imelda, 2024)
Anemia is a condition where the concentration of hemoglobin in the blood is lower than normal, someone who has anemia will experience conditions such as weakness, fatigue, lethargy and loss of concentration. And carried out on students who have experienced menstruation. Research Objectives: To know about the relationship between menstrual patterns and the incidence of anemia in SMA PINK 03 Tambun Selatan students. Methods: The design of this study used an analytical survey with a cross sectional design. Sample: The research sample was 127 students using purposive sampling technique. Research Results: The results obtained in this study were 73 (57.5%) female students who experienced anemia and (52%) 66 female students who experienced abnormal menstruation. The relationship between menstrual patterns and the incidence of anemia in female students through the chi-square test results in a p-value of 0.000, p value < a (0.05). Conclusion: Students who have anemia are likely to experience abnormal menstrual patterns. Suggestion: It is expected that students consume nutritious food and contain lots of iron, even though they experience abnormal menstruation.